(untitled) (The Research of Medical Science Review, 2025)
Child marriage remains a critical public health and human rights challenge in Pakistan, disproportionately affecting rural adolescent girls. This qualitative study explored the physical and psychological health consequences of child marriage in rural Khyber Pakhtunkhwa, with a focus on Nowshera district. Data were collected through focus group discussions with married women, in-depth interviews with survivors, and key informant interviews with healthcare providers and community stakeholders. Thematic analysis revealed five overarching patterns: early pregnancy-related maternal risks, chronic nutritional deficiencies, and obstetric complications; psychological distress including depression, anxiety, trauma-related symptoms, and social isolation; intergenerational impacts on children’s physical and emotional well-being; barriers to healthcare access due to stigma, gender norms, and economic dependence; and long-term consequences such as chronic illness and diminished self-worth. The findings underscore the intersection of socio-cultural practices, economic precarity, and weak service infrastructure in perpetuating cycles of harm. The study highlights the urgent need for integrated interventions addressing both maternal and mental health outcomes of child marriage, community-based prevention strategies, and effective enforcement of legal frameworks. By situating these findings within Pakistan’s socio-legal and global development agenda, the study contributes context-specific evidence to advance progress towards Sustainable Development Goals 3 and 5.